What is the evidence for chemical thromboprophylaxis in foot and ankle surgery? Systematic review of the English literature. Issue 3 (September 2015) - Mangwani, Jitendra; Sheikh, Nomaan; Cichero, Matthew; Williamson, David
Abstract Venous thromboembolism (VTE) is a well documented complication following lower limb trauma and surgery. The incidence of VTE in hip and knee surgery has been well studied, whereas the incidence in foot and ankle surgery is less clear. There is debate as to which cases require prophylaxis and what is the most effective means by which this is achieved. We performed a systematic review of the published English literature on VTE prophylaxis in foot and ankle surgery using MEDLINE, EMBASE, CINHAL, Cochrane Library, without date restrictions up to December 2012. From 988 citations, 25 papers fulfilled the inclusion criteria. Conclusions were drawn on the incidence (symptomatic and asymptomatic VTE), location (distal vs. proximal), associated risk factors, timing of VTE, role of mechanical and pharmacological prophylaxis and cost effectiveness of the treatment. Our review showed that the overall incidence of symptomatic VTE in foot and ankle surgery is low (0–0.55%). There is increased incidence in foot and ankle trauma patients with the highest incidence reported in tendo-achilles surgery. The reported risk factors include previous history of VTE, immobilisation, high BMI, age, co morbidities, contraceptive pill, and air-travel. There is a cumulative effect resulting in higher risk when two or more risk factors are present.